THE FIRST ARTICLE ABOUT SPORTS IN TURKISH PRESS: ALI FERRUH BEY AND HIS ARTICLE NAMED “FENCING” - Emrah ÇETİN (Fırat University, 2019)
Researchers of sport history indicate that the first article about sport in Turkish press is “Fencing” which was written by Ali Ferruh Bey and published by Servet-i Fünun Magazine in 1891. Although all the studies about the subject in Turkey refer Ali Ferruh’s “Fencing”, it has not been totally analyzed and revealed by any researchers yet. Ali Ferruh Bey wrote “Eskrim” to introduce this sports to Ottomans and publish articles relevant to it in several issues of the magazine. It is known that eskrim became familiar to Ottomans in the middle of the 19. Century and Ali Ferruh Bey’s contributions can’t be denied. In his article “Fencing” which he wrote in Paris and sent to the press in Turkey, his aim was to explain fencing, its benefits, its historical process in India, China, Egypt, Iran and Greece. In this study, not only Ali Ferruh Bey’s article series “Fencing” but also the recognition of fencing as a sport in Ottomans, its being taught in military schools and in Ottoman junior high schools are clarified.